Screen culture a global history - Butsch, Richard 1943- (New directions in media history., 2019)
"Richard Butsch's expansive historical synthesis integrates social, economic, and political history to offer a comprehensive examination of screen media and screen culture globally as they have evolved through the 20th and 21st centuries. Deeply engaging, this is a masterful, integrated global history"--Provided by publisher.